Career Issues of the Female Student-Athlete - Coleman, Victoria D.; Barker, Shirl A. (My University, 1993)
This article discussed the career development needs, issues, and concerns of female student-athletes, a group which faces a variety of problems that are not encountered by male student-athletes. Implications for counseling female student-athletes are identified.
Keywords: career development; sex/gender